'[B]etween power and the people': Journalist-Investigators in Nordic Crime Fiction. (March 2020) - Vuohelainen, Minna
Abstract : Recent Nordic crime fiction contains numerous amateur detectives who are professional journalists. Their presence is partly explained by the shared roots and formal affinities of crime reportage and crime fiction, and by the journalistic backgrounds of many Nordic crime writers. However, the rise of the journalist-investigator as a rival to traditional police detectives is also a mark of growing distrust in the competence of the Nordic welfare state and its officials. Nordic journalist-investigators are typically crusading reporters motivated by a desire to uncover and prevent social injustice, including the neglect and abuse of vulnerable social groups by absent, incompetent or corrupt public officials. In acting as moral guardians of social justice, journalist-investigators carry out the principle of the press as a fourth estate, designed to check state power by publicising abuses of authority, and signal a possible shift from the welfare state towards a civil society. However, this role is also compromised by the ethical dilemmas journalist-investigators face between the demands of uncovering information, protecting vulnerable witnesses, informing the public, preventing crime and meeting commercial imperatives. These conflicts spotlight troubling tendencies within crime fiction and crime reportage: both kinds of writing are underpinned by a narrative structure of anticipation, suspense and dramatic revelation and premised upon the reader's voyeuristic investment in sensational subjects.